2022
DOI: 10.1002/jmri.28508
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of An Association Between Cerebral Blood Flow and Microstructural Integrity in Normative Aging Using a Holistic MRI Approach

Abstract: BackgroundCerebral tissue integrity decline and cerebral blood flow (CBF) alteration are major aspects of motor and cognitive dysfunctions and neurodegeneration. However, little is known about the association between blood flow and brain microstructural integrity, especially in normal aging.PurposeTo assess the association between CBF and cerebral microstructural integrity.Study TypeCross sectional.PopulationA total of 94 cognitively unimpaired adults (mean age 50.7 years, age range between 22 and 88 years, 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This association is present to a greater extent with white matter tissue damage. 26 , 41 , 57 In fact, myelin maintenance through oligodendrocyte metabolism is an energy-demanding process, and therefore myelin homeostasis is particularly sensitive to hypoperfusion and consequent hypoxia or lack of essential nutrients for myelin synthesis. 58 , 59 Recent in vitro studies have shown that oligodendrocytes are substantially more vulnerable to hypoxia and reduced supply of substrates that provide energy as can occur from hypoperfusion, when compared with other glial cells such as microglia and astroglia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association is present to a greater extent with white matter tissue damage. 26 , 41 , 57 In fact, myelin maintenance through oligodendrocyte metabolism is an energy-demanding process, and therefore myelin homeostasis is particularly sensitive to hypoperfusion and consequent hypoxia or lack of essential nutrients for myelin synthesis. 58 , 59 Recent in vitro studies have shown that oligodendrocytes are substantially more vulnerable to hypoxia and reduced supply of substrates that provide energy as can occur from hypoperfusion, when compared with other glial cells such as microglia and astroglia.…”
Section: Discussionmentioning
confidence: 99%
“…6,16,20 This emerging method offers rapid and reliable whole-brain MWF map within feasible clinical time 6,16,20,[31][32][33][34] and has been used in assessing myelin loss in mild cognitive impairment and dementias, as well as examining factors influencing cerebral myelination in normative aging. 16,22,23,26,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] A whole-brain R1 map was also generated from the co-registered SPGR and DAM datasets using DESPOT1, 21 and a wholebrain R2 map was generated from the co-registered bSSFP and DAM datasets using DESPOT2. 21 The DW images were corrected for eddy current using the function eddy in FSL and for motion effects using the affine registration tools as implemented in FSL 30 and registered to the DW image obtained with b=0 s/mm 2 using FNIRT.…”
Section: Data Processingmentioning
confidence: 99%
“…Indeed, recent works have demonstrated that deficits in cerebral blood flow are directly linked to reductions in cerebral tissue integrity. This association is present to a greater extent with white matter tissue damage (25,48,49). In fact, myelin maintenance through oligodendrocyte metabolism is an energy-demanding process, and therefore myelin homeostasis is particularly sensitive to hypoperfusion and consequent hypoxia or lack of essential nutrients for myelin synthesis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Using fast steady-state MRI sequences, namely the spoiled gradient recalled echo (SPGR) and balanced steady-state free precession (bSSFP) sequences, the multicomponent driven equilibrium steady-state observation of T 1 and T 2 (mcDESPOT) [18][19][20][21][22][23] has been introduced for whole-brain high spatial resolution MWF determination within a clinically feasible acquisition time (∼20 min). To improve the accuracy and precision in derived MWF values, the Bayesian Monte Carlo (BMC) analysis of mcDESPOT (BMC-mcDESPOT) was proposed and extensively applied in studies of cerebral maturation and degeneration 12,21,22,[24][25][26] .…”
Section: Introductionmentioning
confidence: 99%